Is COVID-19 multisystem inflammatory syndrome a new variant of Kawasaki Disease? - Khawla Abu Hammour,; Rana Abu Farha,; Qusai Manaseer,; Tasnim Dawoud,; Walid Abu Hammour, (Archives of Rheumatology, 2022)
Objectives: In this systematic review, we aimed to evaluate the clinical features, therapeutic options, and outcomes of children with multisystem inflammatory syndrome in children (MIS-C) and to investigate whether MIS-C is a new variant of Kawasaki disease. Materials and methods: Adhering to PRISMA principles, we searched for eligible studies between December 2019 and June 2020 through the following databases: PubMed, ISI Web of Science, SCOPUS, and Science Direct. Studies including original data of patients aged <21 years with MIS-C and descriptions of clinical signs, laboratory or radiological investigations were selected. Results: A total of 84 studies were identified, for which 48 were eligible for full screening and only 13 studies (n=657) met our inclusion criteria. More than 70% of patients with MIS-C tested positive for severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). The most common symptoms were gastrointestinal (80 to 100%) and most patients presented with fever for >4 days. Mucocutaneous manifestations are similar to Kawasaki disease presented in up to 64% in some studies. Almost all patients had significant elevations in inflammatory markers, and up to 50 to 100% had elevated troponin suggesting myocardial damage. Intravenous immunoglobulin (IVIG) was administered to 60% of patients in 12 studies and 80 to 100% in five studies. Steroids were administered to 10 to 95% of patients. The overall mortality rate was 0.9%. Conclusion: The temporal association between novel coronavirus disease 2019 (COVID-19) onset and Kawasaki-like disease and MIS-C suggests a causal link. Both syndromes have similar cascades of symptoms and hyperinflammation, which likely explain their response to the same immunomodulatory agents. However, it is unclear yet why some children appear more susceptible to develop MIS-C.